QOL-13. THE ROLE OF EPILEPSY IN ELDERLY PATIENTS WITH GLIOBLASTOMA: AN AUSTRIAN MULTICENTER ANALYSIS. (14th November 2022) - Demetz, Matthias; Hecker, Constantin; Krigers, Aleksandrs; Machegger, Lukas; Kerschbaumer, Johannes; Geiger, Philipp; Pöppe, Johannes; Spinello, Antonio; Griessenauer, Christoph; Thomé, Claudius; Freyschlag, Christian; Schwartz, Christoph
Abstract: BACKGROUND: With an aging population, acquisition of a better understanding of prognostic factors in elderly patients with Glioblastoma multiforme (GBM) is of utmost importance. Epileptic seizures have been found to correlate with improved overall survival (OS) in low-grade gliomas; however, the impact of epilepsy in GBM patients on outcome parameters is poorly defined. This study aims at specifically evaluating the impact of epilepsy in elderly GBM patients. Material & METHODS: Two Austrian academic neurosurgical centers retrospectively analyzed all elderly (≥ 65 years) GBM patients with de-novo tumors, who underwent surgery between 09/2006 and 07/2021. Epidemiological, histopathological and survival data were gained from patients' electronic charts and screened for presence of epilepsy preoperatively or during follow-up. Tumor volume was assessed using standardized software. RESULTS: 391 patients (55% males, 45% females) with a median age at surgery of 73 years (IqR 68.5-77.5) were analyzed. The mean predicted OS was 12.4 months (CI95% 10.9-14.0). Mean follow-up was 10.4 months (CI95% 9.1-11.6) in our cohort. Median tumor volume amounted to 26.47 cm 3 (IqR 12.65-43.49). 95 patients (24%) suffered from preoperative epilepsy. 17 (18%) patients showed epilepsy after tumor resection. Four patients (1.0%) showed a worsening of already preoperatively diagnosed seizures. Patients with lower tumor volumes experienced significantly more often seizures compared to patients with larger tumors, p< 0.001. Survival did not correlate with preoperative epilepsy (p > 0.05). However, Cox-regression revealed that multifocal tumor location (HR=1.777, p=0.025) and thalamic involvement (HR=11.121, p=0.030) influenced OS. Surgery-associated complications shortened OS significantly (HR=1.945 [CI95% 1, 296-2, 916], p=0.025). CONCLUSION: Even though epilepsy was not found to directly impact survival in elderly GBM patients, we found that surgery led to epilepsy freedom in a significant proportion of our patient cohort, thereby potentially leading to improved QoL. Greatest focus should be set on avoiding any surgery-associated deficits, since these severely influence the OS.